Pemikiran Pendidikan Islam Berprinsip Filosofis - Sundari Sundari; Dwi Noviani; Komarudin Sassi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
The philosophical basis of Islamic education is essentially identical to the concept of Islamic education philosophy itself, which comes from the same source, namely the Koran and al-Hadith (al-Sunnah).From these two sources, thoughts emerged about Islamic issues in various aspects, including the basic foundations of Islamic Education. Thus, the results of the thinking of 'Ulama such as qiyash and ijma' are the result of thinking from the main sources, namely the Koran and al-Hadith (al-Sunnah).